2020
DOI: 10.1088/1742-6596/1706/1/012171
|View full text |Cite
|
Sign up to set email alerts
|

Exploring popular topic models

Abstract: Information from micro-blogging site such as Twitter is a huge repository of data. A lot of research is happening on sentiments, discovering patterns and prediction. One challenging task is dividing this humongous unstructured data into clusters. Several topic modeling methods are proposed by researchers. This paper presents a brief summary of topic modeling methods LDA, LSI and NMF and their applications. Experiments are conducted on the Twitter based datasets created using tweets on keywords Cauvery river, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…The outperformance of LDA compare to NMF also can be seen in Moreno et al [38], who focused on predicting the Big 5 traits. Our literature review also showed that standard LDA yielded better results compare to LSA in nonpersonality topic modeling study [55]. However, as expected, our experiment indicated that the seed-guided model performed better than nonseeded topic models where the coherence scores of SLDA and GNMF are more than 50 in all the analyses disclosed in Table 4.…”
Section: Performance Comparisonsupporting
confidence: 74%
See 3 more Smart Citations
“…The outperformance of LDA compare to NMF also can be seen in Moreno et al [38], who focused on predicting the Big 5 traits. Our literature review also showed that standard LDA yielded better results compare to LSA in nonpersonality topic modeling study [55]. However, as expected, our experiment indicated that the seed-guided model performed better than nonseeded topic models where the coherence scores of SLDA and GNMF are more than 50 in all the analyses disclosed in Table 4.…”
Section: Performance Comparisonsupporting
confidence: 74%
“…Prior to evaluating the topics generated by SLDA, we used three nonseeded models, namely LDA [40], NMF [55], and LSA [55] as well as a seed-guided model called GNMF [42] to make comparisons with our proposed model. We also conducted an analysis to determine the sensitivity of seed words against the performance of SLDA and GNMF.…”
Section: Performance Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Dalam analisis sentimen dan topic modeling pada data Twitter yang berisi "#IndiaFightsCorona" untuk menganalisis opini publik, LDA berkinerja lebih baik untuk sentimen positif, dan untuk sentimen negatif, LSA berkinerja lebih baik. Eksperimen dilakukan pada kumpulan data berbasis Twitter yang dibuat menggunakan twit dengan kata kunci sungai Cauvery, tagihan Lokpal dan Rahul Gandhi menggunakan metode permodelan topik LDA, LSI dan NMF yang mengevaluasi keakuratan topik yang dibentuk dengan menggunakan langkah-langkah confussion, kemungkinan log, dan koherensi topik dimana topik terbaik yang terbentuk kemudian diumpankan ke model regresi Logistik dan diketahui model yang dibuat menunjukkan akurasi yang lebih baik dengan LDA [6].…”
Section: Jiko (Jurnal Informatika Dan Komputer)unclassified